Political parties in the Philippines from 1900 to the present - Banlaoi, Rommel C.; Carlos, Clarita R. (Makati City, Philippines : Konrad-Adenauer-Stifting, 1996)
The study on Political Parties in the Philippines is a very useful reference to the origin , function and typology of the Philippine parties in general, especially however their story.
1. Theoretical discourse on the meaning, origin, typology and function of political parties -- 2. Pre-colonial period to 1898 -- 3. Early American colonial rule -- 4. American colonial period -- 5. The Commonwealth period -- 6. Japanese occupation period -- 7. Independence period -- 8. Summary and conclusion.
Includes bibliographical references.
Keywords: HISTORY